GOVERNMENTAL POWER CREATING SURVELLIENCE COUNTRY: EXCESSIVE OR ENOUGH - JAIN , Mr. KANISHK; CHAVAN, PRADNYA (IJRDO - Journal of Social Science and Humanities Research, 2019)
The question of the security of the State is always of a grave concern. As technology advances, there are new threats to the nation and this throws up new challenges before the State machinery. To combat these challenges, Section 69 of the Information Technology Act, 2000 was drafted. It provides the Government with the power to monitor decrypt or intercept any information in any computer resource. It also enables the Government to appoint certain agencies to car. The order of government is nothing but establishment of that country in which government tries to control every part of people’s lives which is nothing but making and set up of Orwellian society. Hence it may be concluded by this order that it’s not worth for the people to live in this country. We the people of India also want our country to be safe and secure but there should be some proper, just and fair procedural way to be followed by government. If central and state government agencies don’t stop their so called as lawful activity of interception or monitoring or decryption of information then this small word of seven letters ‘privacy’ going to cause disaster, fraud in the life of people. Thus government activity of securing country can lose the trust of their own citizens. The police is there in police station not in our house so why government want to be our relative for all the time out these functions.